Loperamide: studies on its mechanism of action. Issue 8 (August 1981) - Sandhu, B K; Tripp, J H; Candy, D C; Harries, J T
Abstract : The effects of loperamide on net solute and water absorption, and prostaglandin E2 (PGE2) and cholera toxin-induced secretion were studied in the rat jejunum using an in vivo steady-state perfusion technique. Loperamide stimulated absorption of fluid, electrolytes, and glucose and reversed PGE2 and cholera toxin-induced secretion to absorption; this opiate analogue had no effect on cholera toxin stimulation of adenylate cyclase activity or the rise of tissue cyclic AMP (cAMP) concentrations. The opiate antagonist, naloxone, reduced the antisecretory effects of loperamide without affecting tissue levels of cAMP. These results indicate that loperamide inhibits PGE2 and cholera toxin-induced secretion, and that this phenomenon is independent of any direct effect that cholera toxin has on the adenylate cyclase system. The action of naloxone suggests, but does not prove, that loperamide exerts its effect via opiate receptors.